Qualitative exploration of perceived barriers of exclusive breastfeeding among pregnant teenagers in the Greater Accra Region of Ghana - Angela Kwartemaa Acheampong; Makombo Ganga-Limando; Lydia Aziato (BMC, 2022)
Abstract Background The World Health Organization endorses exclusive breastfeeding for the first six months of every child's life since exclusive breastfeeding has the potential of saving thousands of infants' lives. The global exclusive breastfeeding rate among mothers is sub-optimal. This predisposes infants born to teenage mothers to all types of ailments. Therefore, this study explored the factors that inhibit the practice of exclusive breastfeeding as perceived by pregnant teenagers in the Greater Accra Region of Ghana which is an urban area. Methods The study used techniques in qualitative descriptive exploration to collect data from 30 pregnant teenagers through focus group discussions. Six focus group discussions were conducted and each group was made up of five participants. Informed consent was obtained from participants who were 18 years and above as well as parents of participants below 18 years while informed assent was obtained from participants below 18 years after purposive sampling. Interviews were audiotaped, transcribed and data were analysed through content analysis. Results Two major themes and eight sub themes emerged from the data after analysis. Personal related barriers (negative emotional feelings, irrational thinking, perceived health risks to the baby and perceived self-inefficacy) and social related barriers (provider-client interaction, disapproval of exclusive breastfeeding by close relatives, unfriendly workplace policies and social myths) were the perceived factors that discouraged exclusive breastfeeding among teenage mothers. Conclusion Health professionals should be trained to provide culturally sensitive care to teenage mothers in order to promote exclusive breastfeeding. The media, religious leaders and politicians should help debunk misconceptions about breastfeeding expressed by participants in the study.